Tapping informal networks “guanxi” with information and communication technologies : empowering rural doctors in Xi’an, China. - Tran Khanh Phuong. (2010)
The significant investments of governments in the area of ICTs has been concentrated in the delivery of urban-based health information systems (HIS) (Chiasson & Davidson, 2004). However, rural healthcare in China has been neglected during the development of such market-based health services. Thus, this research paper seeks to investigate the effective use of information and communication technologies (ICTs) within the rural healthcare system, specifically in Xi’an, China. The benefits of, and barriers to, the effective use of these ICTs were analysed using the theoretical model -Value of ICTs Model (Chib, Lwin, Ang, Lin, & Santoso, 2008). In particular we assessed the health information needs, the existing healthcare structure, and the use of informal networks—“guanxi”—to acquire health information. Focus group discussions and in-depth interviews (N=74) were conducted over a period of one month from both the urban and rural healthcare sectors in Xi’an. Respondents included village doctors (30), rural patients (10), urban doctors (17), and 17 other stakeholders in the healthcare sector in Xi’an. Analysis of transcripts showed ICT-utilization benefits, including the facilitation of communication, greater time efficiency, and better access to medical information. As suggested by the theoretical model, infrastructural, economic, socio-cultural, and technological vulnerabilities were also observed. In addition, the use of informal networks “guanxi” was found prevalent amongst Chinese rural doctors, particularly in mobile phone and QQ online social network usage. The implications of these findings for research and policy-making are discussed.